Respuesta :

Answer:

D)  [tex]sin(\frac{4\pi }{3} ) = sin(\pi +\frac{\pi }{3} ) = -sin\frac{\pi }{3}[/tex]

Step-by-step explanation:

A)

[tex]sin(\frac{2\pi }{3} ) = sin ( \pi - \frac{\pi }{3} ) = sin\frac{\pi }{3}[/tex]

B)

[tex]cos (\frac{\pi }{6} ) = cos ( \frac{\pi }{2} - \frac{\pi }{3} ) = sin(\frac{\pi }{3})[/tex]

C)

[tex]cos (\frac{11\pi }{6} ) = cos ( \frac{3\pi }{2} + \frac{\pi }{3} ) = sin(\frac{\pi }{3})[/tex]

D)

 [tex]sin(\frac{4\pi }{3} ) = sin(\pi +\frac{\pi }{3} ) = -sin\frac{\pi }{3}[/tex]

ACCESS MORE